2018
DOI: 10.5194/os-2018-103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wave–Current Interactions in a Wind-jet Region

Abstract: Abstract. Wave–Current Interactions (WCIs) are investigated. The study area is located at the northern margin of the Ebro Shelf (northwestern Mediterranean Sea), where episodes of strong cross-shelf wind (wind jets) occur. The aim of this study is to validate the implemented coupled system and investigate the impact of WCIs on the hydrodynamics of a wind-jet region. The Coupled Ocean–Atmosphere–Wave–Sediment Transport (COAWST) modeling system, which use Regional Ocean Model System (ROMS) and Simulating WAves N… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…For instance, wave-current interactions can contribute to the generation of large-amplitude waves, triggered naturally when a stable wave train encounters an accelerating opposing current (Onorato et al, 2011). Ràfols et al (2019) drew a similar conclusion via numerical simulations with coupled (hydrodynamic-wave) models in the NW Mediterranean Sea. Viitak et al (2016) reported an increase of the wave height of up to 100 cm in nearshore waters of the eastern Baltic Sea, during the St. Jude storm, due to the combined effect of surface currents and sea level on the wave field evolution.…”
Section: Research Challengesmentioning
confidence: 78%
“…For instance, wave-current interactions can contribute to the generation of large-amplitude waves, triggered naturally when a stable wave train encounters an accelerating opposing current (Onorato et al, 2011). Ràfols et al (2019) drew a similar conclusion via numerical simulations with coupled (hydrodynamic-wave) models in the NW Mediterranean Sea. Viitak et al (2016) reported an increase of the wave height of up to 100 cm in nearshore waters of the eastern Baltic Sea, during the St. Jude storm, due to the combined effect of surface currents and sea level on the wave field evolution.…”
Section: Research Challengesmentioning
confidence: 78%